FRI0284 EFFECTIVENESS AND SAFETY OF SECUKINUMAB IN NAÏVE OR TNF-INHIBITORS FAILURE PSORIATIC ARTHRITIS PATIENTS IN REAL LIFE: A 24-MONTHS PROSPECTIVE MULTICENTER STUDY. (2nd June 2020) - Lorenzin, M.; Carletto, A.; Foti, R.; Chimenti, M. S.; Semeraro, A.; Costa, L.; Santo, L.; Fracassi, E.; Montanari, I.; Felicetti, M.; Fonti, G. L.; Caso, F.; et al.
Abstract : Background: Secukinumab (SEC) is a novel treatment for psoriatic arthritis (PsA), but data from real life are still missing. Objectives: 1)to evaluate the effectiveness and safety of a wide cohort of PsA patients on SEC followed in 7 Italian rheumatologic centers for 24 months;2)to compare the features and disease activity indices of SEC-treated PsA patients subdivided in naïve biological drugs (group A ) and in TNF-inhibitors (TNFi) failure patients (group B ). Methods: Consecutive patients with moderate-severe PsA, who begun SEC treatment were evaluated prospectively.Data on disease characteristics, previous and ongoing treatments, comorbidities and duration of follow-up were collected.Disease activity, functional and clinimetric scores and biochemical values were recorded at baseline (t0), at 6 (t6), 12 (t12), and 24 (t24) months.Anova (Kruskal Wallis) and generalized linear models were used to compare variables over time.Infections and adverse events were also collected. Results: PsA 345 patients [38.84% men;mean age 52.9 (11.27) years] were enrolled;mean treatment duration was 18.53 (9.97) years.SEC was prescribed as first line biologic treatment in 133 (38.55%) patients and as second or more line biological treatment in 212 (61.45%) patients. Enthesitis was present as a prominent manifestation in 61.44% of patients (Figure 1 ).In all population significant decrease in tender/swollen joints;Visual Analogue Scale of pain (VASp) and general health (VASgh);Psoriasis Area Severity Index (PASI);Leeds Enthesitis Index (LEI);number of dactylitis;Health Assessment Questionnaire modified for spondyloarthritis (HAQ-S);Bath Ankylosing Spondylitis Disease Activity Index (BASDAI);Bath Ankylosing Spondylitis Functional Index (BASFI);C-reactive protein (CRP) was achieved.Effectiveness of all PsA patients was associated to an improvement in Ankylosing Spondylitis disease activity score (ASDAS) [t0=3.45 (0.69) vs t24=1.48 (0.23);p<0.01] and in Disease Activity in PsA (DAPSA) [t0=29.52 (12.56) vs t24=11.41 (7.63);p<0.001].At t0 group B had a more erosive (p=0.04) and polyarticular pattern (p=0.04), a longer disease duration (p=0.001), a greater prevalence (p=0.04) of psoriasis and dactylitis (p=0.01), a higher PASI score (p=0.01), while no significant difference was observed for uveitis, inflammatory bowel diseases, enthesitis.At t24 group A showed better physical functioning and lower disease activity compared to group B [HAQs A vs B=0.03 (0.16) vs 0.69 (0.73);BASDAI A vs B=2.37 (0.66) vs 4.27 (2.33);ASDAS A vs B=1.4 (0.62) vs 1.99 (0.86);CRP A vs B=2.03 (1.94) vs 3.11 (1.55) mg/L;DAPSA A vs B=7.03 (3.57) vs 12.41 (8.05)].After t24 of treatment 74.6% of Group A and 72.8% of Group B articular had an inactivedisease activity (MDA), accordingly to ASDAS and DAPSA respectively.Forty-three patients (12.46%) stopped the treatment during the follow-up mainly because of primary or secondary loss of efficacy (29 and 24, respectively).Only 14 patients suspended SEC because of adverse events (of which 9 for reactions at site of injection).A low number of episodes of mild infections (16) occurred;SEC was instead permanently discontinued in 7 cases for:oral refractory mucositis (3);recurrent aphthosis (2);diverticulitis (2).The retention rate at t24 was good in the whole population.Interestingly no differences were found between Group A and B (p=0.815). Conclusion: In a real life clinical setting, SEC was safe and effective in PsA. as shown by a significant decrease of DAPSA and ASDAS over a 24-months follow up. Disclosure of Interests: Mariagrazia Lorenzin: None declared, Antonio Carletto: None declared, Rosario Foti Consultant of: lilly, sanofi, MSD, Janssen, Abbvie, BMS, celgene, roche, Speakers bureau: lilly, sanofi, MSD, Janssen, Abbvie, BMS, celgene, roche, Maria Sole Chimenti: None declared, Angelo Semeraro: None declared, Luisa Costa: None declared, Leonardo Santo: None declared, Elena Fracassi: None declared, Ilaria Montanari: None declared, Mara Felicetti: None declared, Giulia Lavinia Fonti: None declared, Francesco Caso: None declared, Andrea Doria Consultant of: GSK, Pfizer, Abbvie, Novartis, Ely Lilly, Speakers bureau: UCB pharma, GSK, Pfizer, Janssen, Abbvie, Novartis, Ely Lilly, BMS, Augusta Ortolan: None declared, Roberta Ramonda Speakers bureau: Novartis, Celgene, Janssen, Pfizer, Abbvie, Lilly